Rancang Bangun Aplikasi Sistem Pendukung Keputusan Penilaian Siswa Berprestasi Menggunakan Metode MFEP - Wijana, Miki; Ahmad, Ilham Maulana (INTERNAL (Information System Journal), 2025)
The assessment of outstanding students is an important aspect of education aimed at recognizing academic and non-academic achievements. However, in practice, this process is often time-consuming and prone to subjectivity when conducted manually. Therefore, a decision support system (DSS) is needed to assist in making objective and structured decisions. This study aims to design and develop a decision support system for evaluating outstanding students using the MultiFactor Evaluation Process (MFEP) method. The MFEP method is used to evaluate alternatives (students) based on several assessment criteria with predefined weights. The system was developed using the Agile approach, which includes analysis, design, implementation, and testing stages. The results show that the system can automatically process student assessment data and generate final rankings that match manual calculations. System testing confirmed that all functions performed well and helped make the selection process faster, more accurate, and more transparent.